2022
DOI: 10.2141/jpsa.0210104
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Mediated Regulation of Sperm Fertilization Potential in Poultry

Abstract: Fertilization requires successful completion of molecular events taking place at different spatiotemporal scales. Transcriptionally and translationally inactive sperm need to rely on pre-assembled pathways modulated by extracellular signals that traverse the plasma membranes. However, species differences in how sperm respond to them delay the progress toward a comprehensive understanding of how activation of the signaling cascades is coordinated in poultry sperm. In chickens, recent studies have found that mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Genetic factors may be instrumental in regulating SM ( Froman, et al, 2002 ; Jarrell, et al, 2020 ). Studies have suggested that sperm motility is primarily regulated by intracellular signal transduction processes, including G protein-coupled receptors, adenylate cyclase ( AC ), ion channels, ATP, and flagellation-related proteins ( Böttinger, 2010 ; Miller, et al, 2015 ; Asano and Priyadarshana, 2022 ; Murat, et al, 2023 ). These molecules and pathways regulate the ion balance in sperm cells, structure and movement of the cytoskeleton, and flagellar swing, ultimately impacting sperm motility, and fertilization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic factors may be instrumental in regulating SM ( Froman, et al, 2002 ; Jarrell, et al, 2020 ). Studies have suggested that sperm motility is primarily regulated by intracellular signal transduction processes, including G protein-coupled receptors, adenylate cyclase ( AC ), ion channels, ATP, and flagellation-related proteins ( Böttinger, 2010 ; Miller, et al, 2015 ; Asano and Priyadarshana, 2022 ; Murat, et al, 2023 ). These molecules and pathways regulate the ion balance in sperm cells, structure and movement of the cytoskeleton, and flagellar swing, ultimately impacting sperm motility, and fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…The testes are the site of spermatogenesis, maturation, and storage ( Estermann et al, 2021 ). Unlike mammals, bird sperm can acquire fertilization capacities within the testes, highlighting the critical role of testicular function in SM development ( Asano and Priyadarshana, 2022 ).…”
Section: Introductionmentioning
confidence: 99%